IMPLEMENTATION OF PAULUS HENDRIKUS JANSSEN’S PASTORAL TECHNIQUES IN THE MISSION WORK OF STP IPI ALUMNI IN MALANG DIOCESE - Gulo, Helena; Riyanto, Eko Armada; Bonusu, Yeremias (Universitas Sanata Dharma, 2024)
Pastoral work requires certain techniques or strategies. The success of such work depends on how accurately the techniques or strategies the pastoral agent selects and uses. One of the pastoral theologians who introduced pastoral strategies was Father Paulus Hendrikus Janssen, CM. This research focuses attention on the implementation of Paulus Hendikus Janssen's pastoral strategy in the pastoral work of STP IPI alumni who work in the Malang Diocese. In an effort to obtain data related to this theme, the approach used was qualitative, using an interview method with several alumni involved in pastoral work in the Malang Diocese. The research results show that there is implementation of Paul Janssen's pastoral strategy by alumni of the Indonesian Pastoral Institute Pastoral College in the Diocese of Malang. This is practiced, because there are many benefits to be gained, namely they know the context of the mission better, understand the problems of the people in depth, there is a lot of local wisdom and religious wealth that is discovered and is useful for developing the faith of the people, there is a mission framework that is structured by following a pattern. -pattern developed by Paul Janssen. Apart from the benefits, there are also challenges and difficulties that must be overcome by pastoral agents. This research is expected to contribute to the development of pastoral patterns in the Malang diocese in particular and in Indonesia in general. At a theoretical level, Paul Janssen's pastoral strategy enriches the knowledge of pastoral theology.